Production and Physiological Characters of Soybean Varieties Under Drought Stress with Application of Nitrogen Sources - Yaya Hasanah; Tengku Chairun Nisa; . Hapsoh; Hamidah Hanum (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Soybean  is  a  legume  sensitive  to  drought  conditions  resulting  in  decreased  yield  and  seed quality.  Drought stress on plants also inhibits nitrogen uptake.  The objective of the research was to  determine production and physiological characters  of soybean varieties under drought stress through nutrient N management. This research used a randomized block design with  3 factors  and  3  replications.  The  first  factor  was  soybean  varieties  (Anjasmoro,  Wilis  and Sinabung). The second factor was drought stress conditions consisted of 50%, 60% , 70% and 80%   of field capacity (FC). The third factor was the application of N consisted of (1). Without application of N fertilizer (control);  (2). N fertilizer dose of recommendation (50 kg Urea/ha); (3). Inoculation of Bradyrhizobium sp. ; (4). Organic N sources (straw compost 10 tons/ha)  ; (5).  Organic  N  sources  (farmyard  manure  10  tons/ha).  The  results  suggest  that  Anjasmoro variety  improved dry weight of seed per plant compared with Willis and Sinabung.   Increased drought stress ( 80-50 % of FC) resulted in a decrease in dry weight of seed per plant. Sources  of  N  in  the  form  of  urea  or  Bradyrhizobium  sp.  increased  the  dry  weight  of  seeds  per  plant compared  with  treatment  N  sources  straw  and  manure  compost.  The  interaction  between Bradyrhizobium sp.  or Urea and Anjasmoro variety improved  dry  weight of seeds per plant